A Sensitive, Specific and Simple Loop Mediated Isothermal Amplification Method for Rapid Detection of Campylobacter spp. in Broiler Production - Quyen, Than Linh; Nordentoft, Steen; Vinayaka, Aaydha Chidambara; Ngo, Tien Anh; Engelsmenn, Pia; Sun, Yi; Madsen, Mogens; Bang, Dang Duong; Wolff, Anders (Frontiers in Microbiology, 2019)
Campylobacteriosis is one of the most common foodborne diseases worldwide. Two Campylobacter species - Campylobacter jejuni (C. jejuni) and Campylobacter coli (C. coli) in poultry and poultry products are considered to be the main source of human campylobacteriosis. Therefore, studying Campylobacter status in poultry flock is needed in order to prevent transmission of disease and reduce human risk, health cost, and economic losses. In this study, we adapted and used a Loop-Mediated Isothermal Amplification (LAMP) assay for specific, sensitive, simple and cost-effective rapid detection of C. jejuni and C. coli in the poultry production chain. By using optimized conditions for amplification and a small, low-cost commercial blue LED transilluminator for detection, a limit of detection (LOD) of 1 CFU/ reaction was achieved for testing of C. jejuni and C. coli in spiked chicken feces. The method took less than 70 min from receiving the samples to the final results (including 30 min for amplification). Comparison results of the LAMP and real-time PCR methods showed a relative accuracy, specificity, and sensitivity of 98.43%, 97.87%, and 100%, respectively. Cohen's kappa index also showed an excellent agreement between the two methods. The LAMP was used to study Campylobacter status in broiler flocks during the production of five weeks. The results showed that the method was specific, sensitive and was suitable to develop for online rapid detection of Campylobacter spp. at poultry production.